Research in education and concepts of knowledge: the production of knowledge in question - Almeida, Natalia Regina (Universidade Estadual de Campinas, 2014)
In the field of knowledge in education, discussion about the treatment given to its definition as a field, investigative object and different possibilities theoretical-methodological, epistemological, was frequent in the last decades of the twentieth century. In this perspective, the aspects that relate to the process of construction and production of research in the field of education and knowledge of different theoretical and methodological possibilities deserve more theoretical and conceptual investment. Thus, this paper, from the literature, aims to present a brief discussion of the different conceptions of knowledge in the construction of research in the field of knowledge in education and two theoretical and methodological positions the practice of educational research. As a final consideration, the intention of this article is not to exhaust the issue in question, for there are many issues that permeate the practice of educational research.